Combination of inhaled nitrous oxide and oral opioids induces long-lasting analgesic effects in patients with neuropathic pain: ProtoTOP study post hoc exploratory analyses. Issue 9 (20th September 2022) - Bouhassira, Didier; Perrot, Serge; Attal, Nadine; Ramirez-Gil, Juan Fernando; Delval, Cécile; Schaller, Manuella; Bessière, Baptiste; Houéto, Patrick; Sommer, Claudia
Abstract : The long-lasting analgesic effects of nitrous oxide/oxygen mixture inhalations in patients with neuropathic pain are significantly larger in patients receiving opioids as a concomitant treatment. Abstract: Experimental studies have suggested that nitrous oxide-induced analgesia depends on interactions with opioids. On the basis of these results, we hypothesized that the effects of inhaled nitrous oxide/oxygen (N2 O/O2 ) 50%-50% equimolar mixture (EMONO) on patients with neuropathic pain would be higher in those receiving concomitant opioids. To test this hypothesis, we did exploratory post hoc analyses of our recently published ProtoTOP study to compare the effects of EMONO and placebo in patients with or without concomitant opioid treatment. A total of 92 patients of the 221 (ie, 41.6%) included in the ProtoTOP study were concomitantly treated with opioids. In contrast with our previous analyses, average pain intensity was significantly decreased in comparison with placebo one week after the last treatment administration in patients treated with opioids, but not in those treated without opioid, and this effect was maintained over the 4-week follow-up period. Neuropathic pain symptom inventory (NPSI total and subscores) was also significantly more decreased after inhalation of EMONO in comparison with placebo only in patients receiving opioids. The proportion of patients with at least 30% pain reduction and of those reporting an overall improvement with the Patient Global Impression of Change were significantly higher only in this population of patients. In conclusion, these results complement our previous analyses with the identification of a specific population of responders to EMONO inhalation in patients with neuropathic pain. As suggested by experimental studies, we hypothesized that these long-lasting analgesic effects could depend on the anti-N-methyl-D-aspartate properties of N2 O.